AN ANALYSIS OF IDIOMATIC EXPRESSION FOUND IN ADELE’S LYRICS SONG - Anastasia Ema Gunawan; Eripuddin (JEE (Journal of English Education), 2019)
The purpose of the research was to find out the idiomatic expression and to find out the contextual meaning of idiom expression which are used in Adele’s lyrics song. The technique of analyzing the data the researcher used descriptive qualitative. Qualitative research referred to the meaning, concepts, definitions, symbols and description of the things. There are 56 idiomatic expression found in 3 types of idiom those are Phrasal verb idiom, Tournure idiom and Irreversible Binomial idiom. Whereas another idiom could not be found by the researcher during the analysis. This research found the menaing of idiom expression moast as a contextual meaning. The researcher hopes that’s this thesis will be useful for both theoretical and practical source in learning how to translateEnglish Idiom and also for those who conduct further study about analysis of idiomatic expression.